Natural phenomena as indices of the forest-dwellers’ ecological calendar (2014)
This article presents an inventory of the knowledge of the forest-dwellers (rural inhabitants of the Amazon forest, who live in the forest and from the forest and its waters) of the lower Ucayali River region (Peruvian Amazon) about the astronomical, climatological, hydrographic and biological phenomena, with which they locate themselves in the seasonal rhythms and guide their activities in the natural environment. Forest-dwelling populations distinguish two main periods: the time of lower waters or sunny season, and the time of rising waters of rainy season. These two periods are divided into four seasons: Small Dry Season (May-June, descending waters), Great Dry Season (July-October), Small Rainy Season (November-December, rising waters), and Great Rainy Season (January-April). It includes a glossary with the biological identification and definitions of 183 names of plants and animals and terms and expression in local Spanish.